An integrated transcriptomic and metabolic phenotype analysis to uncover the metabolic characteristics of a genetically engineered Candida utilis strain expressing δ-zein gene - He, Qiburi; Gong, Gaowa; Wan, Tingting; Hu, He; Yu, Peng (Frontiers in Microbiology, 2023)
Candida utilis (C. utilis) has been extensively utilized as human food or animal feed additives. With its ability to support heterologous gene expression, C. utilis proves to be a valuable platform for the synthesis of proteins and metabolites that possess both high nutritional and economic value. However, there remains a dearth of research focused on the characteristics of C. utilis through genomic, transcriptomic and metabolic approaches. With the aim of unraveling the molecular mechanism and genetic basis governing the biological process of C. utilis, we embarked on a de novo sequencing endeavor to acquire comprehensive sequence data. In addition, an integrated transcriptomic and metabolic phenotype analysis was performed to compare the wild-type C. utilis (WT) with a genetically engineered strain of C. utilis that harbors the heterologous δ-zein gene (RCT). δ-zein is a protein rich in methionine found in the endosperm of maize. The integrated analysis of transcriptomic and metabolic phenotypes uncovered significant metabolic diversity between the WT and RCT C. utilis. A total of 252 differentially expressed genes were identified, primarily associated with ribosome function, peroxisome activity, arginine and proline metabolism, carbon metabolism, and fatty acid degradation. In the experimental setup using PM1, PM2, and PM4 plates, a total of 284 growth conditions were tested. A comparison between the WT and RCT C. utilis demonstrated significant increases in the utilization of certain carbon source substrates by RCT. Gelatin and glycogen were found to be significantly utilized to a greater extent by RCT compared to WT. Additionally, in terms of sulfur source substrates, RCT exhibited significantly increased utilization of O-Phospho-L-Tyrosine and L-Methionine Sulfone when compared to WT. The introduction of δ-zein gene into C. utilis may lead to significant changes in the metabolic substrates and metabolic pathways, but does not weaken the activity of the strain. Our study provides new insights into the transcriptomic and metabolic characteristics of the genetically engineered C. utilis strain harboring δzein gene, which has the potential to advance the utilization of C. utilis as an efficient protein feed in agricultural applications.